Tracer study of the office administration graduates of University of Rizal System - Tanay Campus school year 2012-2013 to school year 2017-2018 - Bardoc, Georgie Nacario; Damot, Helen Penolio; Tejada, Kim Chaztine Endaya; Cadion, Esmeralda P. (2018)
This study was conducted to determine the status of work of the Office Administration graduates from schoolyear 2012-2013 to schoolyear 2017-2018. The study made use of descriptive research method. The respondents of the study were the Office Administration graduates of the University of Rizal System - Tanay Campus from Schoolyear 2012-2013 to Schoolyear 2017-2018. The results showed that in terms of the profile, most of the respondents are single, female and belonged to the age-bracket of 21-25 years old. Most of them are currently employed as permanent with a family income of P15,000 to P20,000. In terms of major line of business where they are employed, education had the highest number of frequency. Moreover, salary and benefits are the reasons for staying in the job and the relatedness of the same to their special skills is the main reason for accepting the job. Communication skills were considered the most useful competency, while the degree/ course or major taken was the most useful qualification for employment. Most of the respondents' economic problem included high cost of living, while the social problem identified was limited or no time at all for social activities. Better employment opportunities were considered by the respondents as the possible solution on socio-economic problem. The researchers recommend that the graduates ·should improve more of themselves professionally and personally by attending and participating in trainings and seminars. The school should improve communication skills by providing more trainings/ exercise in language subject especially in English. The school must design an additional/ advance subject/curriculum most especially in communication, human relation and clerical skills because based on the study it was the useful competencies in acquiring a job. Furthermore, this will be a means of reducing the unemployment condition of the graduates by meeting the demand of job offered by the business and industry. The students should be goal-oriented for them to prioritize their career and look for more opportunities to improve by joining course-related activities. The future graduates should be aware of the upcoming activities/ trainings/ seminar of any government agency by information given by means of social media and advance technology information that focuses on job hunting and other employment related. Both graduates and the school administration should keep in touch and by means of annual conducting of similar study will help them monitor the progress and development of the performance of BSOA graduates.
Thesis
Includes bibliographic references
Keywords: University of Rizal System -- Tanay Campus -- Alumni and alumnae